Telos: a pedagogical practice constructed from a didactic simulator - Santos, Graciliano da Silva; Andrade, Alecsandro Michael de; Macheti, Tania Cristina Impocetto; Rocha, Zenaide de Fátima Dante Correia (Revista Hipótese, 2019)
This article investigates contributions in the apprehension of knowledge, autonomy and values used in meaningful pedagogy. It is based on the development of the students' abilities and competences to attend activities of the school curriculum, with teacher mediation in the classroom. By understanding that the teaching and learning process is complex and individual, the relevance of a pedagogical practice with didactic simulators provokes a scenario capable of reading and interpreting a reality that can overcome the frontier of knowledge. Reflecting on the importance of didactic simulators, it becomes paramount as practice in the construction of social responsibility..
Keywords: Didactic Simulator; Skills; Competence; Social Responsability